2023
DOI: 10.1186/s13011-022-00511-0
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of quality of outpatient care use, associated sociodemographic and clinical characteristics, and adverse outcomes among patients with substance-related disorders

Abstract: Background This study identified patient profiles in terms of their quality of outpatient care use, associated sociodemographic and clinical characteristics, and adverse outcomes based on frequent emergency department (ED) use, hospitalization, and death from medical causes. Methods A cohort of 18,215 patients with substance-related disorders (SRD) recruited in addiction treatment centers was investigated using Quebec (Canada) health administrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…This study was conducted in accordance with the Declaration of Helsinki and approved by the Douglas Mental Health University Institute ethics committee (IUSMD [20][21][22][23][24][25][26].…”
Section: Institutional Review Board Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted in accordance with the Declaration of Helsinki and approved by the Douglas Mental Health University Institute ethics committee (IUSMD [20][21][22][23][24][25][26].…”
Section: Institutional Review Board Statementmentioning
confidence: 99%
“…The typologies pertaining to ED users with psychiatric disorders have mostly focused on the socio-demographic and clinical characteristics of high ED users, mostly finding them to be young, single, male, and with medical comorbidities, but few typology studies have examined patient service use patterns [23,24]. One recent Canadian study that identified three profiles regarding the quality of outpatient care use for patients with SRDs found that the profile with the most frequent ED use and hospitalizations was made up of high outpatient service users mostly affected by psychiatric disorders and personality disorders [25]. Another study identified three profiles of moderate ED users with psychiatric disorders: one composed of young males with SRDs who were low outpatient service users; one of middle-aged females with common psychiatric disorders; and one of older patients with cooccurring psychiatric disorders-chronic physical illnesses.…”
Section: Introductionmentioning
confidence: 99%